Knowledge, attitude and practices of Malay traditional medicine practitioners towards Covid-19 pandemic in Malaysia - Zainal, Illy Zahzlin; A. Rahman, Nor Azlina; Mohd Shafri, Mohd Affendi (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Restricted movement and preventive actions such as vaccination had been introduced in Malaysia to break the chain of transmission of the new coronavirus, COVID-19. These strategies, however, affected many sections of the society including Malay medicine practitioners. Malay medicine practitioners are important as they could also influence the response of the society towards health promotion by the mainstream modern medicine authority. This, however, depends on their own level of knowledge, attitude and practices concerning COVID-19 pandemic. Methods: A cross-sectional study using convenience sampling by online questionnaire was conducted among Malay traditional medicine practitioners in Malaysia. Results: This study showed that the level of knowledge was high (n=90, 89.1%) while the level of attitude was moderate (n= 66, 65.3%) and practice was moderate (n=55, 54.5%). Age and marital status were significantly associated with knowledge scores with the p-value of 0.001 and 0.010 respectively. None of the socio-demographic characteristic appeared to have an association with attitude and practice. Strong and significant correlation were found between knowledge and attitude (r = 0.230, p-value = 0.020), and attitude with practice (r = 0.395, p-value = 0.001) of the Malay traditional medicine practitioners concerning COVID-19. No correlation was found between knowledge and practice as p>0.05. Conclusion: The results would be useful for formulating policies that are suitable to this important and influential group of healthcare providers to reduce resistance and increase compliance to strategies concerning COVID-19 in society.